Analisa Pengaruh Technology Readiness Index Pada Penggunaan E-Wallet - Arvin Hardianto; Mona Fronita; Medyantiwi Rahmawita M; Arif Marsal (Bulletin of Computer Science Research, 2025)
Current technological developments have also driven transformation in payment systems, one of which is through the implementation of a non-cash lifestyle digital wallet, such as DANA, an application used as a medium for storing and transacting electronic money via smartphone devices. Although the number of DANA users and transaction values ??have shown a significant increase, the adoption of technology does not always have a positive impact. There are still problems, one of which is that some users report delays in incoming balances. The success of implementing technological innovation is influenced by various factors, one of which can be measured using the Technology Readiness Index (TRI) instrument developed by Parasuraman. This study aims to identify factors that inhibit the use of DANA Digital Wallets in Indonesia. The results of the analysis using SPSS version 26 software show that the TRI value is at 3.00994 which is included in the moderate category, proving that the resulting influence is standard, with the highest value on the Discomfort variable (0.77892) and the lowest value on the Insecurity variable (0.72978).